Effective diffusion tensor computed by homogenization - Nguyen, Dang Van; Grebenkov, Denis; Poupon, Cyril; Bihan, Denis Le; Li, Jing-Rebecca Li (Diffusion Fundamentals, 2013)
The convergence of the long-time apparent diffusion tensor of diffusion magnetic resonance imaging (dMRI) to the effective diffusion tensor obtained by mathematical homogenization theory was considered for two-compartment geometric models containing non-elongated cells of general shapes. A numerical study was conducted in two and three dimensions to demonstrate this convergence as a function of the diffusion time.